2021
DOI: 10.3390/cancers14010156
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after Surgical Treatment of Metastatic Disease in the Adrenal Gland; Valuable for the Patient?

Abstract: The adrenal glands are common dissemination sites for metastasis of various solid tumors. Surgical treatment is often recommended because targeted therapies and immunotherapy are frequently ineffective for adrenal metastasis. We report the experience with short-term and long-term surgical outcomes of patients undergoing surgery for adrenal metastasis in two hospitals. A retrospective, multicenter study was performed to analyze patient characteristics, tumor-related data, perioperative outcomes, and oncological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…The median follow-up was 13.4 months, ranging from 0 to 124 months, and the median OS was 19 months, ranging from 0.4 to 171 months. The median total dose was 36Gy(10-70Gy) and the median number of fraction was 4.5 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The median dose per fraction was 7.5Gy, ranging from 2 to 30Gy, and the median BED10 was 71.4Gy, ranging from 20 to 180Gy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median follow-up was 13.4 months, ranging from 0 to 124 months, and the median OS was 19 months, ranging from 0.4 to 171 months. The median total dose was 36Gy(10-70Gy) and the median number of fraction was 4.5 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The median dose per fraction was 7.5Gy, ranging from 2 to 30Gy, and the median BED10 was 71.4Gy, ranging from 20 to 180Gy.…”
Section: Resultsmentioning
confidence: 99%
“…Targeted local therapies are gaining popularity as ablative therapy may improve outcomes in patients with limited systemic disease burden (1,2). A paired analysis of 62 patients with isolated AM found that SBRT and laparoscopic adrenalectomy had similar outcomes and survival rates (4), but complications occurred in 37.9% of patients, including ileus or gastroparesis, wound problems, pneumonia, and heart arrhythmia (5). Stereotactic body radiation therapy (SBRT) enables conformal delivery of ablative radiation doses using single or a small number of fractions, resulting in a more effective radio biologic dose (6).…”
Section: Introductionmentioning
confidence: 99%